Towards the strength-ductility synergy of Al2O3/Al composite through the design of roughened interface. (1st November 2021) - Zhang, Zhiming; Fan, Genlian; Tan, Zhanqiu; Zhao, Haitao; Xu, Yanjin; Xiong, Dingbang; Li, Zhiqiang
Abstract: In the study, a roughened interface is designed to achieve the strength-ductility synergy of Al2 O3 /Al composites fabricated by flake powder metallurgy. The roughened SiO2 @Al2 O3 platelets are fabricated by high-shear dispersion process and subsequent sintering at the high temperature. The results show that different morphologies of asperities on the surface of SiO2 @Al2 O3 platelets can be obtained via controlling the sintering time. As the roughness increases, the strength and ductility of SiO2 @Al2 O3 /Al composites are simultaneously improved. Load transfer efficiency is enhanced by platelet-matrix interlocking at the roughened SiO2 @Al2 O3 /Al interface, compared to Al2 O3 /Al composite with smooth Al2 O3 –Al interface. The improved tensile ductility in SiO2 @Al2 O3 /Al composite is attributed to the extrinsic toughening mechanism. This design strategy offers a simple and promising approach to improve the mechanical properties of metal matrix composites. Graphical abstract: Image 1 Highlights: The SiO2 @Al2 O3 platelets are fabricated by high-shear dispersion process and subsequent high temperature sintering. Different roughness on the surface of SiO2 @Al2 O3 platelets are obtained via controlling the sintering time. Load transfer efficiency is enhanced by platelet-matrix interlocking at the roughened SiO2 @Al2 O3 /Al interface. The improved tensile ductility in SiO2 @Al2 O3 /Al composite is attributed to the extrinsic toughening mechanism.